Relation Between Job Stress Dimensions and Job Satisfaction in Workers of a Refinery Control Room - Mehdi Behjati Ardakani; Mehdi Zare; Sakineh Mahdavi; Mohsen Ghezavati; Hossein Fallah; Gholamhossein Halvani; Shahram Ghanizadeh; Alireza Bagheraat (Shahid Sadoughi University of Medical Sciences, 2013)
Introduction: Job stress can result from an imbalance between job demands and the abilities to cope them. Stress can affect individuals and lead to job dissatisfaction. This study was conducted to assess the influence of different job stress dimensions on job satisfaction in workers of a refinery control room located at the south of Iran. Materials & Methods: In this cross sectional study all 100 workers of an oil refinery control room were studied. Job stress and job satisfaction was measured using standard questionnaires provided by national institute of mental health (NIMH) and Robbins respectively. After collecting, data were analyzed using SPSS ver.16 software. A general linear model was used to estimate the effect of different job stress dimensions on the job satisfaction. Results: In this study 62.08 percent of workers were categorized as having high level of stress. In job satisfaction case, 9.2, 27.6, 28.7, 16.1 and 18.4 of workers were classified as totally dissatisfied, dissatisfied, not satisfied nor dissatisfied, satisfied and totally satisfied, respectively. A Pearson correlation test revealed a significant negative correlation between job satisfaction and all studied dimensions of job stress (p= 0.01). In the general regression model, partial Eta squared was 0.03, 0.3 and 0.23 for respectively interpersonal relationships, physical conditions of work and job interest. Conclusion: This study showed that job satisfaction is mostly influenced by physical conditions and job interest dimensions of job stress. Therefore, for improvement of job satisfaction in workers, different parameters of these two dimensions of job stress should be considered.